Краснолаковая пелика из раннесарматского погребения у с. Лиманское - Карнаух, Е.Г.; Данилко, Н.М. (Археологія і давня історія України, 2010)
В научный оборот вводятся материалы раскопок
кургана у с. Лиманское Скадовского района Херсонской области. Особый интерес представляет впускное
погребение раннесарматского времени с краснолаковой пеликой. Стаття вводить до наукового обігу новий поховальний комплекс ранньосарматського часу. Особливий
інтерес являє червонолакова пеліка. На підставі аналогій пеліці та поховальному обряду комплекс з кургану
біля с. Лиманське датується І ст. до н. е. та прекрасно доповнює археологічну карту ранньосарматських
пам’яток Північного Причорномор’я. This article deals with new burial complex of the Early
Sarmatian period (Limanskoe, near Skadovsk, Kherson
region, Ukraine). The red-painted pelica from the burial
is of special interest. Pelicae of this kind from the Early
Sarmatian burial contexts in the Lower Volga region and
the funeral arrangement as a whole correspond to I c. BC.
Hence, the data in question contains some remarkable additional
information concerning spatial distribution of the
Early Sarmatian sites in North Pontic zone.